(untitled) (Journal of history-rus, 2023)
Annotation According to the concept of the information society, modern technical means are the driving force behind the social development of society. That is, the emergence of new types of interaction systems, communication affects the development of society and leads to a new level of culture and civilization. Communication is the process of spreading information, knowledge, spiritual values, moral and legal norms over a large space with the help of technical means. The development of mail on the territory of the Russian Empire led to the emergence of new road systems, which influenced the establishment of security and order in them. And in the late 19th and early 20th centuries, the development of railways and other modes of transport increased the level of communication, raising the postal and telegraph service to the state and international level. This raised the level of intercultural and interethnic relations and made it possible to integrate the space we are considering into events and processes of a global, imperial scale. The purpose of the article is to study the place of postal transportation, post offices in the Semirecheye region, as a form of communication in the integration of regions. Based on this, the main issues explored in the article are the impact of the development of the postal service in the Semirecheye region (in the second half of the 19th century) on establishing relations with the Russian Empire, integration into the general large imperial system and economic, social, cultural results. The international practices of the postal service are also considered. It is studied how the relationship between the colonial state and the metropolis was reflected in the postal service. The structural elements of the general postal-administrative system, the algorithm of postal transportation are differentiated and the specific features of the region are determined. Keywords: communication, post, telegraph, postal roads, means of communication, zemstvo post.